Investigation of locomotive syndrome improvement by total hip arthroplasty in patients with hip osteoarthritis: A before-after comparative study focusing on 25-question geriatric locomotive function scale. - Shigeaki Miyazaki; Kurumi Tsuruta; Saori Yoshinaga; Yoshinori Fujii; Amy Hombu; Taro Funamoto; Takero Sakamoto; Takuya Tajima; Yoshihiro Nakamura; Hideki Arakawa; Jun Nakatake; Etsuo Chosa (PLoS ONE)
Background The 25-Question Geriatric Locomotive Function Scale (GLFS-25) is one of the tests used to assess the risk of locomotive syndrome (LS). It is a comprehensive tool for measuring LS improvement after total hip arthroplasty (THA) and provides beneficial information for rehabilitation after THA. The primary objective of this study was to clarify LS improvement in patients with hip osteoarthritis (OA) who have undergone unilateral primary THA using GLFS-25. A secondary objective was to identify the impact of THA on each specific GLFS-25 item for optimizing functional recovery. Methods The participants of this study were 273 patients who underwent primary THA for hip OA. LS was evaluated using the GLFS-25, stand-up test, and two-step test before receiving THA and three months after THA. Results Before THA, items rated as "moderately difficult" (score ≥2) in GLFS-25 included pain-related Q3 and Q4, activities of daily living (ADL)-related Q12, Q13, Q15, and Q18, and social function-related Q21 and Q23. At three months after THA, these subjective symptoms showed significant improvement. Further analysis of the relationship between these subjective symptom improvements and LS improvement revealed that all items, except pain-related Q3, were significantly associated with LS improvement. Conclusions Patients experienced not only severe hip pain and physical discomfort but also significant difficulties with activities of daily living (ADL) and social participation before THA. LS improvement after THA was strongly associated with improvements in the subjective symptoms of ADL and social functioning. Based on these findings, rehabilitation strategies that focus on enhancing mobility, improving ADL and social engagement, and optimizing gait function after THA are crucial for further supporting LS recovery.